2013
DOI: 10.1007/s13187-013-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cervical Cancer Screening for a Multiethnic Population of Women in South Texas

Abstract: Cervical cancer is a preventable disease. Precancers can be identified and treated through cervical screenings. The HPV vaccine prevents precancers from becoming cancers. The aim of the A Su Salud Cervical Cancer Prevention Program was to apply well-understood health promotion techniques and increase the rate of cervical cancer screening among a high-risk, multiethnic, low-income population in South Texas. Qualitative research was used to identify uptake barriers and tailor media messaging. Using existing reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The interventions were implemented by public or private screening programs, university-based research teams, or health care centers or units. The most common reminder strategies used were text message reminders [29][30][31][32][33][34][35][36][37][38][39][41][42][43][46][47][48][49][50][51][52][53][54][55][57][58][59][60][61][62][63][64][65]. Educational strategies most commonly included general health information about the specific cancer and information about cancer screening, including the importance of screening.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The interventions were implemented by public or private screening programs, university-based research teams, or health care centers or units. The most common reminder strategies used were text message reminders [29][30][31][32][33][34][35][36][37][38][39][41][42][43][46][47][48][49][50][51][52][53][54][55][57][58][59][60][61][62][63][64][65]. Educational strategies most commonly included general health information about the specific cancer and information about cancer screening, including the importance of screening.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%
“…While some studies have shown that interventions using tailored print materials have led to increases in screening for breast [22], colorectal, and cervical cancers [23,24], other studies have found that these materials did not increase CRCS adherence, although they did lead to significant increases in intention to be screened [25,26]. In a recent study, patients who received a computer-delivered tailored intervention coupled with a primary care visit were more likely to complete CRCS compared to those who received a nontailored brochure [27] while another study found that a personally tailored interactive multimedia computer program was more effective than a non-tailored electronic leaflet at increasing CRCS readiness and self-efficacy, but actual screening adherence was not evaluated [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another novel intervention used a family-focused educational approach to improve literacy and screening among Latina, Black, and Arab women (Williams et al, 2013). Targeted automated phone reminders and mass media messaging have been used to improve screening uptake among diverse groups of women, as well (Fornos, Urbansky, & Villarreal, 2014; Michielutte et al, 1989). A review of such cervical cancer prevention programs showed that community outreach is effective, as are targeted patient mailings and Pap test cost reduction programs, and in some cases physician prompts have improved screening and follow-up of abnormal Pap tests (Marcus & Crane, 1998).…”
Section: Introductionmentioning
confidence: 99%